ORIGIN AND CHRONOLOGICAL ANALYSIS OF SHIVA IMAGES IN THE MALWA REGION IN INDIAN ART TRADITION AND HISTORY (WITH SPECIAL REFERENCE TO THE PARAMARA PERIOD) - Batham, Khushboo; Bharadwaj, Kumkum (International Journal of Research -GRANTHAALAYAH, 2026)
The tradition and history of Indian art are very ancient. We see art as a particularly important means of acquiring knowledge. From ancient times, we observe the emergence of art alongside the mental development of humankind. Art encompasses a vast field, within which sculpture holds a unique place among the various art forms. Sculpture reflects the influences of social life and expresses religious and moral ideals. It also embodies beauty and spirituality. The depiction of Shiva has been evident in religious beliefs since prehistoric times, from rock paintings and Indus Valley seals to the art of various dynasties across India. While Shiva is depicted throughout India in both lingam and anthropomorphic forms, the Malwa region, considered the heartland of India, stands out due to the abundance and development of Shaivite temples, making this area seem imbued with the spirit of Shiv. The title of this research paper is " The origin and chronological analysis of Shiva sculptures from the Malwa region in the context of Indian art tradition and history (with special reference to the Parmar period)" It sheds light on the connection between the Parmara rulers and Shaivism, their religious beliefs, and their devotion to Lord Shiva in the Malwa region. Various inscriptions mention land grants for the construction of Shiva temples, as well as the worship and creation of idols during the time of the Parmara kings. The paper then describes the initial construction and artistic characteristics of the Parmara-era Shiva sculptures. Some of the early sculptures are described in detail with the help of illustrations.